THE INFLUENCE OF SERVICE QUALITY, PRODUCT INNOVATION, AND LOCATION ON CUSTOMER SATISFACTION AT KING FRIED CHICKEN IN LHOKSEUMAWE CITY - Aina Shakila; Jullimursyida Jullimursyida; Heriyana Heriyana; Rahmaniar Rahmaniar (PT. Intelek Cendikiawan Nusantara, 2025)
The globalization era has driven significant changes in people's lifestyles, including the growing interest in fast food. King Fried Chicken, as a local culinary business, faces the challenge of fulfilling customer satisfaction amid intense competition. This study aims to analyze the influence of service quality, product innovation, and location on customer satisfaction at King Fried Chicken in Lhokseumawe City. This research employs a quantitative approach using a survey method involving 126 respondents and is analyzed through multiple linear regression with the assistance of SPSS. The results indicate that all three independent variablesservice quality, product innovation, and locationhave a positive and significant effect on customer satisfaction. Fast and friendly service, attractive menu innovations, and a strategic location have proven to be important factors in shaping customers’ positive perceptions. The conclusion of this study suggests that management should continue improving service quality, updating products creatively, and maintaining easily accessible business locations to strengthen customer loyalty and enhance business competitiveness..